Recovery, Ambitions, and Aspirations: An Exploratory Project to Build a Recovery Community by Generating a Skilled Recovery Workforce. Issue 1 (2nd January 2016) - Best, David; Beswick, Tracy; Hodgkins, Steve; Idle, Matt
ABSTRACT: A fundamental barrier to recovery is "negative recovery capital" in the form of barriers to access to housing and paid employment. Stable recovery rests not only on overcoming acute dependence, but also subsequently on developing supportive social networks, a safe place to live, meaningful activities, and a sense of purpose and hope. In the United Kingdom, the recovery movement has faced a huge challenge in translating early recovery into stable recovery because of limited access to housing and employment, and because of stigmatization of those in recovery. This article reviews a social enterprise model for engaging recovering people with an addiction in a building program linked to recovery housing, which also provides employment. The article is based on observations, in-depth qualitative interviews, and focus groups with participants in the program, and describes the social contagion of hope and the elevated aspirations associated with working and generating recovery housing. This model offers inspiration about personal transformation and aspiration that also contributes to the development of a therapeutic landscape of recovery.